Quantitative susceptibility mapping‐based cerebral metabolic rate of oxygen mapping with minimum local variance. Issue 1 (10th March 2017) - Zhang, Jingwei; Cho, Junghun; Zhou, Dong; Nguyen, Thanh D.; Spincemaille, Pascal; Gupta, Ajay; Wang, Yi
Abstract : Purpose: The objective of this study was to demonstrate the feasibility of a cerebral metabolic rate of oxygen (CMRO2 ) mapping method based on its minimum local variance (MLV) without vascular challenge using quantitative susceptibility mapping (QSM) and cerebral blood flow (CBF). Methods: Three‐dimensional multi‐echo gradient echo imaging and arterial spin labeling were performed in 11 healthy subjects to calculate QSM and CBF. Minimum local variance was used to compute whole‐brain CMRO2 map from QSM and CBF. The MLV method was compared with a reference method using the caffeine challenge. Their agreement within the cortical gray matter (CGM) was assessed on CMRO2 and oxygen extraction fraction (OEF) maps at both baseline and challenge states. Results: Mean CMRO2 (in µmol/100 g/min) obtained in CGM using the caffeine challenge and MLV were 142 ± 16.5 and 139 ± 14.8 µmol/100 g/min, respectively; the corresponding baseline OEF were 33.0 ± 4.0% and 31.8 ± 3.2%, respectively. The MLV and caffeine challenge methods showed no statistically significant differences across subjects with small ( < 4%) biases in CMRO2 and OEF values. Conclusions: Minimum local variance–based CMRO2 mapping without vascular challenge using QSM and arterial spin labeling is feasible in healthy subjects. Magn Reson Med 79:172–179, 2018. © 2017 International Society for Magnetic Resonance in Medicine.